(untitled) (Al-Academy, 2019)
substitution is considered a method of meaning enrichment and is a formal substitution for the letter or the word inside the text, and it is an expression substitution that is a replacement of an element of a text with a formal or graphic element, and a substitution of a latter form by a previous vocalization, thus it results in a cohesive expression. Replacement inside the text happens through the existing relation between the word or the letter and the form within the phenomenon that is based on enhancing the meaning in a way that delimits the context. There are many studies and researches written about replacement, especially in the textual linguistics that focused on the literary and linguistic texts. Hence, the researcher found that this concept can be applied on design and its artistic structure that is formed of parts. Thus, the research is made into chapters, the first chapter determined the problem which is stated in the following question: What is the role of the formal substitution in enhancing communication discourse in the logo design? The research objective is (discovering formal substitution methods and what it achieves). The theoretical framework consists of three sections: the first one (the concept of substitution, substitution in Art). The second section (logo formal substitution, types of formal substitutions). The third section addressed (the logo design, types of logos). Two research models have been described and analyzed based on the analysis items that are drawn from the theoretical framework and the resulting indicators. Then the researcher presented the results and conclusions reached at including: The formal substitution in the structure of the logos contributes in strengthening the functional side through the expressive aspect of the iconic picture and its simulation of the reality which would contribute in the speed of communication between the logo and the receiver as is the case in all the models. The researcher arranged the recommendations in the lights of the results of the research such as: • The need for the Iraqi sport institutions to pay attention to design sport logos keeping pace with the scientific development in the design field and the logo in particular through hiring academic and specialized designers. The research ended with a list of relevant resources and an abstract in English